2005
DOI: 10.1002/ppap.200500002
|View full text |Cite
|
Sign up to set email alerts
|

Economical Advantages of Low‐Pressure Plasma Polymerization Coating

Abstract: Summary: Low‐pressure plasma polymerization coating, as described in this paper, is an ultimately green process that uses a minimum amount of substances and produces a minimum amount of effluent and hence does not require an environmental remediation process. The super‐green aspect of the processing entirely changes the equation for the viability of the process in industrial applications. The main hampering factors for the low‐pressure processes are 1) psychological fear of vacuum processes, 2) relatively high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…One such material, linalyl acetate, a principle component of essential oils such as Lavandula angustifolia, is an environmentally friendly, non-synthetic material, and in conjunction with plasma polymerisation provides a completely 'green' product fabricated via safe and cost effective methods. The benefits of such films and techniques in industry has been recently discussed by Yasuda [21]. This material has been a subject of recent study into its optical and morphological characteristics [22], as well as its influence over the growth and optical characteristics of an n-type organic semiconductor [23].…”
Section: Introductionmentioning
confidence: 99%
“…One such material, linalyl acetate, a principle component of essential oils such as Lavandula angustifolia, is an environmentally friendly, non-synthetic material, and in conjunction with plasma polymerisation provides a completely 'green' product fabricated via safe and cost effective methods. The benefits of such films and techniques in industry has been recently discussed by Yasuda [21]. This material has been a subject of recent study into its optical and morphological characteristics [22], as well as its influence over the growth and optical characteristics of an n-type organic semiconductor [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples include permanent hydrophilic treatments of textiles or contact lenses and the formation of carboxylated surfaces which can serve as platforms for the immobilization of bioactive molecules for biointerfaces (in which case already low densities of functional groups are sufficient). [1][2][3][4][5] Although acrylic acid is often used as monomer for plasma polymerization, mixtures of hydrocarbons with carbon dioxide might show some advantages. [6,7] Experimental series using hydrocarbon monomers show a complex behaviour of the deposition rate as a function of the energy input, where often a drop in deposition rate is reported at higher plasma energies.…”
Section: Introductionmentioning
confidence: 99%
“…Such surfaces are of importance for controlled deposition of nanoobjects, for applications in biology, or sensors. In this context, polymers deposited by plasma polymerization have proved to be relevant since they present the following inherent advantages: i) the plasmachemical surface functionalization step is substrate-independent (Boening, 1988), ii) the plasma polymer thin film provides a good adhesion with most of the substrates (Roucoules et al, 2007), iii) the surface density of immobilized molecular species can be finely tuned by varying the pulsed plasma duty cycle (Teare et al, 2002;Oye et al, 2003) and iv) the plasma polymerization step is easily scaled up to industrial dimension (Yasuda & Matsuzawa, 2005). It was recently demonstrated that Deep-UV lithography could be used to generate topography patterns at the surface of maleic anhydride-based plasma polymers with typical dimension down to 75 nm .…”
Section: Wwwintechopencommentioning
confidence: 99%